2008
DOI: 10.1016/j.ejpn.2007.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Neuromotor development in infants with cerebral palsy investigated by the Hammersmith Infant Neurological Examination during the first year of age

Abstract: Our results point out that the HINE can give additional information about neuromotor development of infants with CP from 3-6 months of age, strictly related to the gross motor functional abilities at 2 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 25 publications
3
53
0
10
Order By: Relevance
“…Most of the children who participated in the present study were male and that fact has often been reported in the literature 14,15 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Most of the children who participated in the present study were male and that fact has often been reported in the literature 14,15 .…”
Section: Discussionmentioning
confidence: 72%
“…other studies report that diplegic children are the majority 14,[18][19][20] . diplegia affects principally, or especially the lower limbs because of the serious injury in periventricular areas and subcortical white matter; its main causes are cerebral ischemic and hemorrhagic phenomena and fetal or post-natal hydrocephaly especially in preterm newborn children 5,17 .…”
Section: Discussionmentioning
confidence: 99%
“…New risk factors have appeared among infants who previously would have died, and the incidence of neurodevelopmental impairments in survivors of NICU is higher than in normal birth-weight newborns. In particular, due to the high risk of interventricular haemorrhage and periventricular leukomalacia, an increasing prevalence of cerebral palsy has occurred in premature, low birth-weight newborns and children born with asphyxia (Romeo D, Cioni, Scoto, Mazzone, Palermo & Romeo M, 2008).…”
Section: Prevalence and Causesmentioning
confidence: 99%
“…According to the severity of motor damage, patients may later show signs of tetraplegia, diplegia, our hemiplegia, involving, respectively, four members, limited to lower limbs and/or a hemibody (FLETT, 2003;DAMIANO, ABEL, ROMNESS et al, 2006;ROMEO, CIONI, SCOTO et al, 2008;CROMPTON, GALEA and PHILLIPS, 2007). The existent tonic changes may lead, due to encephalopathy, to spasticity, athetosis, dystonic coreoathetosis, or ataxia, with variation according to which areas and regions of the CNS have been harmed (PALISANO, ROSENBAUM, WALTER et al, 1997;DAMIANO, DODD andTAYLOR, 2002, DAMIANO, ABEL, ROMNESS et al, 2006;SCHOEN, RICCI, and OLIVEIRA, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral palsy (CP) can be defined as a non-progressive, variable, and stable encephalopathy stemming from a pre-natal, peri-natal, post-natal lesion which can compromise the central nervous system's (CNS) neuromaturation period (FLETT, 2003;ROMEO, CIONI, SCOTO et al, 2008;SCHOEN, RICCI, and OLIVEIRA, 2003;SOUZA and FERRARETO, 1998). Epidemiological studies in developed countries demonstrate that there is a prevalence of 1.5 to 2.5 cases for every thousand births (SOUZA and FERRARETO, 1998;BEGNOCHE and PITETTI, 2007).…”
Section: Introductionmentioning
confidence: 99%